REVITALISASI PENDIDIKAN ISLAM UNTUK MENCETAK PEMIMPIN MASA DEPAN - Melani Indriawati; Raihan Naufal Rahman; Rafah Parhatusshafwah; Faiz Fikri Al Fahmi (Cahaya Ilmu Bangsa Institute, 2025)
The revitalization of Islamic education is a strategic step in shaping future leaders with strong character, professional competence, and solid moral values. This study employs a literature review approach to explore the challenges, opportunities, and strategies for revitalizing Islamic education. The findings reveal that Islamic education faces globalization challenges, including moral crises, technological gaps, and the lack of curriculum relevance to contemporary needs. Therefore, integrating Islamic values with modern science and technology, along with innovative teaching methods, is essential. The study also emphasizes the importance of synergy between families, schools, and communities in creating a supportive educational environment. Moreover, government involvement and cross-sector collaboration are key to improving the quality of Islamic education through policy support, infrastructure, and funding. With a holistic and value-based approach, Islamic education can produce leaders with noble character, global competitiveness, and a commitment to serving humanity's welfare.